Social context and literature sociological functions in the novel about you by tere liye - S, Meirysa; Wardarita, Ratu (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
The purpose of this study was to describe the author's social context and socio-cultural elements in the novel About You by Tere Liye. This research was a qualitative research with sociology of literature approach. This research was to describe author's social context and socio-cultural elements in the novel About You by Tere Liye. The results of the discussion in this study were obtained story fact that related to their social values namely violence, starting a business, product marketing, malaria events (January 15 disasters), friendship, and betrayal. While the social values contained in the novel About You by Tere Liye included: patience, obedience, forgiveness, helping others, caring for others, working hard, loyalty, mutual trust between friends, help between friends, and honestly. The results of this study conclude: (1) author's social context of the novel About You by Tere Liye work consists of the theme and facts of theory, and (2) socio-cultural elements of the novel About You the moral values contained in Tere Liye's novel About You are: (a) human relationships with self that include fear, death, longing and revenge, (b) human relationships with humans.